Haruki Murakami's First Person Singular. Twilight Stories and Autobiographical Traces - Castellón Alcalá, Heraclia (2023)
The volume First person singular –appeared in 2020– includes eight short stories by Murakami that allow us to discover topics already covered in his repertoire: vital confusion, distasteful episodes of an unhappy youth, the irruption of the fantastic, imposture. Checking how the issues raised are reflected and the selected textual format is the objective of this work. In addition to verifying its link with the previous works, it is important at the same time to recognize what new contribution this short story collection offers, for which reason the new territories that are traversed have been reviewed. The tone from which it is narrated stands out here, now that of old age. We thus find that he reflects on the neighbourhood of inexorable death, as well as he also presents codes of moral principles, all always from the perspective of a first person singular from which Murakami seems to give us both personal and fictitious clues, with the appearance of truth, that the Japanese genre of I Novels offers him, to which he says he somehow refers.